Quantum Control for Nanoscale Spectroscopy With Diamond Nitrogen-Vacancy Centers: A Short Review - Hernández-Gómez, Santiago; Fabbri, Nicole (Frontiers in Physics, 2021)
Diamond quantum technologies based on color centers have rapidly emerged in the most recent years. The Nitrogen-Vacancy (NV) color center has attracted a particular interest thanks to its outstanding spin properties and optical addressability. The NV center has been used to realize innovative multi-mode quantum-enhanced sensors that offer an unprecedented combination of high sensitivity and spatial resolution at room temperature. The technological progress and the widening of potential sensing applications has induced an increasing demand for performance advances of NV quantum sensors. Quantum control (QC) plays a key role in responding to this demand. This short review affords an overview on recent advances in QC-assisted quantum sensing and spectroscopy of magnetic fields.